The framework for effective collaboration between public training institutions and private industries in the context of National Dual Training System (NOTS) environment in Malaysia - Rashidi, Ramli (2011)
The introduction of National Dual Training System (NDTS) in the Malaysian VET system to develop self-reliant and highly skilled workers to continually meet technological advancement needs of the industry is indeed timely. The Malaysian government wants to ensure the private industry and public training institutions (J'UTRI) collaborate successfully towards developing the desired human resource talent pool capable of raising the income and economic status of the country to international standard. The private industries and PUTRI should be inspired and guided by the national human resource vision and collaborate through the dual system by sharing resources, expertise, facilities, information, and funds to develop the highly skilled workers. The purpose of this study is mainly to identify the key factors that have the strong potential to fonn the effective framework for the desired collaboration between public training institutions and private industries. With such framework the collaborative partners can ensure that the dual system implementation can benefit the learning process of their apprentices whose sucdess will be paramount to serve the interests of all parties involved, including those of our national interests. This research will identify several key factors that will form the framework for the dual system collaboration. The identified key factors are namely, a) Goal setting, b) Partnership* development, c) Collaboration management, d) Impact of learning and competence, e) Evaluation of collaborative performance and dual system in use. This research engaged 23 interviews, 100 survey questionnaires and 4 focus group discussions and workshops. The results showed that the significant factors such as the importance of goal-setting, development of partnerships, partnership management, the impact of learning and skills development are most critical in the formation of collaboration hamework. Finally, the recommended framework has been subjected to rigorous scrutiny and gained approval by both practitioners and experts that it is applicable to our NDTS collaboration.